2006
DOI: 10.1063/1.2161926
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial investigation of the isolated nanoparticle to coalescent layer transition in a gradient sputtered gold nanoparticle layer on top of polystyrene

Abstract: Within a combinatorial investigation, a gradient sputtered gold layer on top of polystyrene on silicon substrate is addressed. Results from a real-space inspection by transmission electron microscopy are compared with surface-sensitive microbeam grazing incidence small-angle x-ray scattering. The combinatorial approach allows distinguishing different morphologies prepared under exactly the same environmental conditions on one single substrate. The transition of a coalescent layer to an isolated nanoparticle la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
67
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 17 publications
1
67
0
Order By: Relevance
“…Previous measurements performed on sput- tered gold thin films have shown that it is possible to resolve the scattering form factor of such particles and to characterize their structural correlations. 36 Figure 5͑c͒ is the image showing the 2D GISAXS pattern recorded during this experiment. One clearly sees the very strong wings developing in the q y direction in the scattering pattern.…”
Section: Injection Of Gold Nanoparticlesmentioning
confidence: 99%
“…Previous measurements performed on sput- tered gold thin films have shown that it is possible to resolve the scattering form factor of such particles and to characterize their structural correlations. 36 Figure 5͑c͒ is the image showing the 2D GISAXS pattern recorded during this experiment. One clearly sees the very strong wings developing in the q y direction in the scattering pattern.…”
Section: Injection Of Gold Nanoparticlesmentioning
confidence: 99%
“…The angle of incidence was ␣ i = 0.543°. The resulting footprint on the sample of 0.3ϫ 32 m 2 reduced the beam size compared to previous microbeam and submicrobeam GISAXS experiments 5,6 up to a factor of 10.…”
mentioning
confidence: 70%
“…The angle of incidence was ␣ i = 0.543°. The resulting footprint on the sample of 0.3ϫ 32 m 2 reduced the beam size compared to previous microbeam and submicrobeam GISAXS experiments 5,6 up to a factor of 10.The samples consisted of commercial unconjugated colloidal gold solutions of 2 nm particle size ͑Kisker Biotechnologie͒. Gold nanoparticles are inert and provide strong scattering contrast to the solvent ͑water͒.…”
mentioning
confidence: 99%
See 2 more Smart Citations